O anjo e a besta: Pascal, Machado de Assis e a descristianização do ceticismo - Alex Lara Martins (2018)
The fictional work of Machado de Assis exhibits skeptical components. On the one hand, skepticism is aligned with an intellectual tradition that intends to respond to the 17th century intellectual crisis related to the criteria of faith, truth and natural knowledge. Such a philosophical event would be characterized by revitalizing ancient skeptical arguments in the face of a dispute around the Reformation and the revival of Augustinianism. On the other hand, Machados skepticism is mobilized to explain the morality and social relations of a well-localized community in which knowledge about art and literature was not obtained separately from other embodied cultural capital, such as science and philosophy. Around the written press, Machado de Assiss generation received and produced its artistic, scientific and philosophical acts. The main thesis is that Machados fiction presents an alternative to a tradition that Christianizes skepticism. The paths of this tradition in Brazil were analyzed from the standpoint of the reception of Victor Cousins eclecticism and Pyrrhonian interpretation of Pascal. The questions arising from the historical and philosophical development of the Christianization of skepticism are redirected by Machados fiction. The main consequence of this reflection is what I called the dechristianization of skepticism. Studies of Machados philosophical sources have already singled out Pascal as a major influence. Considering the 19th century Brazilian intellectual background, and its own reception of Pascals thought, I intend to show that the self-reflexive and aporetic developments of the Machadean narratives aimed an ironic reconstruction of a typically Pascalian anthropology. The beastliness of the human being and the view of the opinionated model of social relations are some of the Pascalian themes that fiction urges to dechristianize.